NAVIGATING DIVERSITY: A COMPREHENSIVE EXPLORATION OF INCLUSIVE TEACHING STRATEGIES IN FOREIGN LANGUAGE EDUCATION IN UZBEKISTAN (Web of Teachers: Inderscience Research, 2024)
This article investigates the integration of inclusive teaching strategies within the domain of foreign language education. Recognizing the significance of diversity in language classrooms, we explore a myriad of pedagogical approaches aimed at fostering inclusivity. By addressing linguistic, cultural, and cognitive variations, this research seeks to equip educators with effective tools to create a supportive and enriching environment for diverse learners, thereby enhancing the overall foreign learning experience.